Estimates of genetic parameters for linear body measurements and prediction of body weight in goat. (1st April 2022) - Dige, Mahesh Shivanand; Rout, Pramod Kumar; Singh, Manoj Kumar; Bhusan, Saket; Kaushik, Rakesh; Gowane, Gopal Ramdasji
Abstract: The objective of this study is to estimate genetic parameters for linear body measurements along with their correlation to live weight with a focus on devising a scale to predict live weights from body measurement. A total of 142, 564 records on body measures and live weights were collected from 8701 Jamunapari goats. Genetic parameters were obtained for body length ( L ), height at withers ( H ) and heart girth ( G ) from birth to adult stage by univariate and multivariate analysis using the average information restricted maximum likelihood method. The best model for body measures at birth included the additive effect of animal and dam along with their covariance and maternal environment, whereas for traits measured later in life, the maternal environment was not significant. After accounting for the direct maternal correlation ( r am ), the total heritability estimates for linear body measurements ( L, H and G ) at the preweaning and postweaning stages of growth ranged from 0.14 to 0.20. Significant genetic variability implies further scope for selection. The genetic correlations of live weight at birth, 3, 6, 9 and 12 months with corresponding L, H and G were high in magnitude indicating scope to select animals for higher weight using morphometric measurements. When weighing scales are unavailable in the field, prediction of weight using L and G was recommended [live weight = (0.291 ×  L ) + (0.306 ×  G ) − 16.8]. We recommend the use of body measurements in the Jamunapari goat breeding program owing to their high genetic correlation with corresponding live weights.